The electrical manufacturers, 1875-1900 : - Passer, Harold C. (Harvard University Press, 1953)
This is the 1972 hardback reprint of Passer's 1953 classic. It was published in the 'Technology and Society' reprint series, Daniel J. Boorstin advisory editor. Binding is hardback, silver cloth with 'Technology and Society imprinted in black in three circles on front of volume. Title, Author, and publisher (Arno) printed in black on the spine.